Improving propagation success of D. Melanoxylon (African blackwood) in Tanzania (II): Rooting ability of stem and root cuttings of Dalbergia melanoxylon (African blackwood) in response to rooting media sterilization in Tanzania - Washa, WBA; Nyomora, AMS; Lyaruu, HVM (Tanzania Journal of Science, 2021)
Dalbergia melanoxylon is a plant with valuable wood in the world and therefore is over harvested for timber while its regeneration is very low. The propagation efforts by techniques such as tissue culture or mycorrhiza have not been investigated which instigated conduction of this study. Soil and cuttings were collected from Kilwa, Kilosa and Babati for rooting test, potting media and soil characterization. The results showed that fresh soil improved rooting characteristics while sterilized soil did not due to the presence of mycorrhiza in fresh soil compared to none in sterilized media. The overall rooting in fresh soil in non-mist propagator was higher, 100% for softwood and 37% for root cuttings while none rooted in the open nursery. The results revealed that there was no significant correlation between rooting and collection sites while cutting type and the soil type used significantly influenced rooting. Softwood cuttings that weighed less than 15g significantly increased rooting at (P < 0.05) compared to cuttings that weighed above 15g. It was recommended to propagate Dalbergia melanoxylon using softwood cuttings placed in a non-mist propagator and using fresh soil infected with mycorrhiza. Key words: Dalbergia melanoxylon, non-mist propagator, rooting